Modulatory effect of adenosine receptors on the ascending and descending neural reflex responses of rat ileum - Storr, Martin (BioMed Central, 2002)
BACKGROUND: Adenosine is known to act as a neuromodulator by suppressing synaptic transmission in the central and peripheral nervous system. Both the release of adenosine within the small intestine and the presence of adenosine receptors on enteric neurons have been demonstrated. The aim of the present study was to characterize a possible involvement of adenosine receptors in the modulation of the myenteric reflex. The experiments were carried out on ileum segments 10 cm in length incubated in an single chambered organ bath, and the reflex response was initiated by electrical stimulation (ES). RESULTS: ES caused an ascending contraction and a descending relaxation followed by a contraction. All motility responses to ES were completely blocked by tetrodotoxin, indicating that they are mediated by neural mechanisms. Atropine blocked the contractile effects, whereas the descending relaxation was significantly increased. The A(1 )receptor agonist N6-cyclopentyladenosine increased the ascending contraction, whereas the ascending contraction was reduced by the A(1 )receptor antagonist 8-cyclopentyl-1,3-dipropylxanthine. Activation of the A(1 )receptor further reduced the descending relaxation and the latency of the peristaltic reflex. The A(2B )receptor antagonist alloxazine increased ascending contraction, whereas descending relaxation remained unchanged. For A(2A )and A(3 )receptors, we found contradictory effects of the agonists and antagonists, thus there is no clear physiological role for these receptors at this time. CONCLUSIONS: This study suggests that the myenteric ascending and descending reflex response of the rat small intestine is modulated by release of endogenous adenosine via A(1 )receptors.